Securing digital documents using digital watermarking - Hammoud, Awad Kadhim; Mohaisen, Hatem Nahi; Shaker, Qusay Samir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The intellectual property of digital documents has been protected by using many methods of digital watermarking. Digital documents have been so much of advantages over print documents. Digital documents are less expensive and easy to store, transport, and searched compared to traditional print documents.  But it has its owner limitation too. A simple image editor can be used to modify and make a forged document. Digital documents can be tampered easily. In order to utilize the whole benefits of digital document, these limitations have to overcome these limitations by embedding some text, logo sequence that identifies the owner of the document..In this research LSB  technique  has been used to embedding Digital watermarking , the proposed method consist of two major part: the embedding part and extraction part. The BMP picture type has been used in embedding process for accuracy  and uncompressed image, and it is the best type in  embedding process. This technique used to discover the genuine documentThe experiments show the proposed technique has 100% accuracy in authenticating the genuine document and Multimedia content security.